Myxoid Liposarcoma of the Greater Omentum. Case Report and Literature Review - Alexander Marchena Rodríguez; Flavia Linares Tovar; Jorge Carlos González Fariñas (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Liposarcoma is a malignant tumor of mesodermal origin derived from adiposetissue. It is the most frequent of the soft tissue sarcomas in adults. Themost frequent location is in the lower extremities, the abdominal is rare.It reaches enormous proportions. Treatment is surgery with completerresection for local control of the disease. The case of a patient whopresented due to ultrasound finding of an intra-abdominal tumor in thehypogastrium of unspecified origin, with asymptomatic evolution, ispresented. Physical examination revealed a palpable tumor process towardsthe hypogastrium of approximately 3cm, smooth, mobile, non-superficial, notpainful on palpation. Elective exploratory laparotomy was performed, withtotal omentectomy for tumor on the free edge of the greater omentum. Biopsyreported the presence of myxoidliposarcoma of the greater omentum. Due tothe infrequency of this type of injury, it was decided to present the caseof this patient.